Orientasi Ekonomi Petani Perempuan dalam Pemenuhan Nafkah Keluarga di Bontokadatto Kabupaten Takalar - Nur Afni; St. Junaeda (Jurnal Ekonomi dan Riset Pembangunan, 2023)
This study aims to determine the role, position, and economic orientation of female farmers in the Bontokadatto Village, which makes the agricultural sector a source of fulfilling the family's economic livelihood. This study used a descriptive qualitative approach with a case study type of research, with data collection techniques through observation, interviews and documentation/documentation. As well as the purposive sampling technique with the characteristics of sampling through certain criteria, the considerations in this study involved 8 informants. The results of this study indicate that: (1) Women in the Bontokadatto Village do not only work in the domestic sector, but also play a role in supporting the economic aspect in seeking additions by participating in the agricultural sector (2) Female farmers in Bontokadatto Village both have husband status and single parents make the agricultural sector the main source of fulfilling their family's living. (3) Double Burden or multiple roles are mentioned together with the concept of cultural dualism, namely the concept of the domestic sphere (domestic environment) and the public sphere (public environment), and (4) The coping strategy of female farmers in Bontokadatto Village applies three adaptations, namely: active adaptation, passive adaptation and tissue adaptation.